Associations of Visual Function With Cognitive Performance in Community-Based Older Adults: The Eye Determinants of Cognition Study. Issue 10 (20th November 2021) - Arsiwala, Lubaina T; Guo, Xinxing; Ramulu, Pradeep Y; Sharrett, A Richey; Mihailovic, Aleksandra; Swenor, Bonnielin K; Mosley, Thomas; Dong, YaNan; Abraham, Alison G
Abstract: Background: Given the detrimental impacts of visual and cognitive impairment separately, in older adults, understanding their coexistence could inform strategies against age-related cognitive changes. Methods: Participants from Washington County (White) and Jackson (Black) sites of the Atherosclerosis Risk in Communities Study were recruited who differed on racial, regional, urbanicity, and community-based factors. Presenting distance visual acuity (DVA; representing vision loss due to disease or lack of eye-care), corrected DVA (representing optimal correction for refractive loss of vision), and contrast sensitivity were measured. Factor scores for global cognition, memory, executive function, and language domains were calculated for 3 visits. We quantified the associations of vision measures with change in cognitive scores, stratified by community/race, using generalized estimating equations. Results: In 982 participants, mean (standard deviation [ SD ]) baseline age was 74 (4) years, with 37% males and 45% Jackson/Black participants. As hypothesized, after accounting for potential confounders, in the better-eye, worse presenting DVA was associated with greater 10-year decline rate in global cognition, memory, and executive function in Washington County/White participants (eg, global cognition: −0.08 SD [95% confidence interval: −0.12, −0.04]). Worse corrected DVA was associated with greater 10-year decline rate in executive function in Washington County/White participants (−0.10 SD [−0.15, −0.04]). Better contrast sensitivity was associated with lower 10-year decline rate in global cognition and executive function in Washington County/White participants (eg, global cognition: 0.10 SD [0.06, 0.14]). None of these associations were confirmed in Jackson/Black participants. Conclusions: Our study supports a functional link between some vision measures and cognition in older adults, but in only 1 of the 2 communities studied.